PENGARUH PERTUMBUHAN DANA PIHAK KETIGA TERHADAP PERTUMBUHAN LABA DENGAN PERTUMBUHAN PEMBIAYAAN SEBAGAI VARIABEL MODERATING PADA BANK SYARIAH DI INDONESIA - Muhammadinah Muhammadinah (TECHNOBIZ : International Journal of Business, 2020)
This research aims to see the influence of the growth of third-party funds to the growth of profit with financing growth as a moderating variable on the sharia Bank in Indonesia. The population and the samples in this study were all bank Sariah's 14 Bank and sharia business units as many as 20 banks using financial statements for 3 years (2017-2019) on a monthly basis so that amounted to 36. The analytical techniques used are moderated regression analysis (MRA). The results showed that financing growth variables were able to moderate the influence between third-party fund growth variables on profit growth.